The One about Coyote going West: mimesis and ethics in multicultural landscapes of Canada and Australia - Polak, Iva (Array, 2011)
Appropriation of indigenous voice and/or subject appropriation (as defined by James O. Young and Susan Haley) in a literary space of the two multicultural postcolonial locations, Canada and Australia, lays bare a very uneasy palimpsest of postcoloniality. Conflation of two different views, that of literary works being the constructs of possible worlds (mimesis), i.e. the space of textual freedom, and literary works being limited by postcolonial ethics especially when they attempt to map the cultural space of the postcolonial other, reveals the setbacks of postcolonial hybridity turning it into a possible minefield. The implications of alleged freedom of creative act is discussed in the context of cultural appropriation leading to various literary “borrowings” and “hoaxes”, and the function of Native/Aboriginal author by showing various views coming from Canadian and Australian Indigenous literati and scholars who most ardently oppose to the outsider’s appropriation of Indigenous imagery. The quote from Thomas King’s seminal short story in the title of the paper serves as a metaphor for a double-bind effect of careless appropriation of Indigenous stories by non-Indigenous writers.